2022
DOI: 10.3389/fimmu.2022.887781
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Myeloid Cells in GBM Immunosuppression

Abstract: Gliomas are intrinsic brain tumors that originate from glial cells. Glioblastoma (GBM) is the most aggressive glioma type and resistant to immunotherapy, mainly due to its unique immune environment. Dimensional data analysis reveals that the intra-tumoral heterogeneity of immune cell populations in the glioma microenvironment is largely made up of cells of myeloid lineage. Conventional therapies of combined surgery, chemotherapy and radiotherapy have achieved limited improvements in the prognosis of glioma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 106 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…Compared to neutrophils in peripheral blood, TANs were enriched with the angiogenesis-related factor S100A9 and MMP9 ( 153 ). Neutrophil-released BV8, S100A8/9, and MMP9 are key factors in activating VEGF-A, thereby promoting angiogenesis ( 159 ). Furthermore, Neutrophils can induce drug resistance in gliomas.…”
Section: Roles Of Neutrophils In Glioma Immunitymentioning
confidence: 99%
“…Compared to neutrophils in peripheral blood, TANs were enriched with the angiogenesis-related factor S100A9 and MMP9 ( 153 ). Neutrophil-released BV8, S100A8/9, and MMP9 are key factors in activating VEGF-A, thereby promoting angiogenesis ( 159 ). Furthermore, Neutrophils can induce drug resistance in gliomas.…”
Section: Roles Of Neutrophils In Glioma Immunitymentioning
confidence: 99%
“…VEGF induced Ang-1 pericytes’ recruitment to improve vascular stability. Moreover, these molecules also participate in the recruitment of myeloid cell populations into GBM [ 26 , 27 ]. Around necrotic zone, Ang-1 is absent because hypoxia down-regulates Ang-1 expression; nevertheless, Ang-1 is more perceived in the tumor periphery [ 28 ].…”
Section: Tumor Microenvironment (Tme) In Gbm Nichesmentioning
confidence: 99%
“…Studies have shown that TAMs are highly implicated in suppressing anti-tumor immune functions of T cells and directly facilitate tumor cell immune escape [ 123 ]. For these reasons, as the higher macrophage infiltration in the TME of GBM is often correlated with poor treatment outcomes and prognosis [ 27 ], depleting them by specifically targeting and killing them is an attractive strategy that was evaluated in the recent past.…”
Section: Therapeutic Strategies Focused On Tams Of Gbmmentioning
confidence: 99%
“…[47,48] As the richest nucleated hematopoietic cells, myeloid cells are the main regulators in glioma immunosuppression. [49] Myeloid cells at an immature status often differentiate into dendritic cells (DCs), macrophages, and granulocytes under normal conditions. However, some regulatory molecules under pathological conditions suppress the maturation of myeloid cells, resulting in the development of myeloid-derived suppressor cells (MDSCs) consisting of granulocytic and monocytic subsets.…”
Section: Healthy Brain Immunology and Glioma-associated Immunosuppres...mentioning
confidence: 99%